Introdução de Ferramentas de Gestão Modernas numa Empresa na Beira (Moçambique): o plano de autocontrolo da Prapesca - Ana Célia Gomes (Cadernos de Estudos Africanos)
An «old» and systematically revisited question, is the one which asks for the possibility of using modern management models and tools in contexts where the premises of scientific management are not present. One may answer this question either negatively or affirmatively. In the first case, it becomes necessary to develop strong context‑bounded models. This option may be quite problematic in terms of productivity and global market integration. In the second case, we may solve the problem in two different ways: either by adopting classical models acritically or «recreating» them. This is the starting point of a discussion about two fundamental questions in African management, responsibility and leadership. The discussion will be illustrated by the Prapesca case, a company which processes and sells fish products, mainly shrimps, and is implementing quality procedures designated as Self‑control Plan. From the suggestive designation of the plan, we are going to reflect about the complexity of modern African business and follow the itinerary of two Portuguese entrepreneurs, forced to create a path between adventure and competitiveness.